Pengaruh Self Assessment System, Ketepatan Pengalokasian, Tarif Pajak Terhadap Tindakan Penggelapan Pajak (Tax Evasion) - Tiara Aenun Khafidah; Dewi Indriasih (Politeknik Harapan Bersama, 2021)
Indonesia as a developing country needs funds to finance expenditures aimed at national development. Taxes are one of the most important elements in supporting the state revenue budget considering that taxes are seen as the largest source of revenue for funds owned by the state which has a very important role, but in fact there are still taxpayers who are not aware of their obligations in calculating, reporting and remitting their taxes as well as the tax evasion which aims to reduce or even eliminate the tax burden owed. So based on this, the making of this journal aims to find out whether the Self Assessmet System, Allocation Accuracy, Tax Rates can affect the occurrence of tax evasion (Tax Evasion). The method used in making this journal is based on the results of previous research journals that discuss tax evasion. So the authors take a red line from the reading of the journal regarding whether the Self Assessmet System, Allocation Accuracy, Tax Rates can affect the occurrence of tax evasion. Based on the results and conclusions, it states that the Self Assessmet System, the accuracy of the allocation has a partial effect on tax evasion, while the variable tax rate, if seen partially, has no effect on tax evasion. When viewed from all three of these variables have a simulate effect on the occurrence of Tax Evasion. It is hoped that the next research research will be able to add other variables so that it can enrich knowledge in the field of taxation.